Bone marrow stroma protects myeloma cells from cytotoxic damage via induction of the oncoprotein MUC1. (20th January 2017) - Bar‐Natan, Michal; Stroopinsky, Dina; Luptakova, Katarina; Coll, Maxwell D.; Apel, Arie; Rajabi, Hasan; Pyzer, Athalia R.; Palmer, Kristen; Reagan, Michaela R.; Nahas, Myrna R.; Karp Leaf, Rebecca; Jain, Salvia; et al.
Summary: Multiple myeloma (MM) is a lethal haematological malignancy that arises in the context of a tumour microenvironment that promotes resistance to apoptosis and immune escape. In the present study, we demonstrate that co‐culture of MM cells with stromal cells results in increased resistance to cytotoxic and biological agents as manifested by decreased rates of cell death following exposure to alkylating agents and the proteosome inhibitor, bortezomib. To identify the mechanism of increased resistance, we examined the effect of the co‐culture of MM cells with stroma cells, on expression of the MUC1 oncogene, known to confer tumour cells with resistance to apoptosis and necrosis. Co‐culture of stroma with MM cells resulted in increased MUC1 expression by tumour cells. The effect of stromal cell co‐culture on MUC1 expression was not dependent on cell contact and was therefore thought to be due to soluble factors secreted by the stromal cells into the microenvironment. We demonstrated that MUC1 expression was mediated by interleukin‐6 and subsequent up‐regulation of the JAK‐STAT pathway. Interestingly, the effect of stromal cell co‐culture on tumour resistance was partially reversed by silencing of MUC1 in MM cells, consistent with the potential role of MUC1 in mediating resistance to cytotoxic‐based therapies.